Favna jamskih hroščev (Coleoptera) Krima (Dinaridi, osrednja Slovenija): zgodovina raziskanosti in favnistična izoliranost - Kapla, Andrej (Acta entomologica slovenica (Ljubljana), 2017)
Cave beetle studies in caves of Mt. Krim, and in the cave Velika Pasica especially, were carried on since mid 19th century, starting with Ferdinand Schmidt, due to close proximity of the Ljubljana city. The cave Velika Pasica is locus typicus for five cave beetle taxa. Altogether ten cave beetle species are known to inhabit the area of Mt. Krim. According to cave beetle fauna, it seems that the area of Mts. Krim and Mokrec represents quite isolated subterranean environment with one endemic species Anophthalmus hirtus and further two endemic beetle taxa Anophthalmus schmidti motschulskyi and Typhlotrechus bilimeki hacqueti. In the paper all known cave beetle species that were found in the area of Mt. Krim are presented: Laemostenus schreibersi, Typhlotrechus bilimeki hacqueti, Anophthalmus hirtus, Anophthalmus schmidti motschulskyi, Anophthalmus scopolii, Aphaobius milleri, Bathyscia montana, Bathysciola sylvestris, Bythoxenus subterraneus and Troglorhynchus anophthalmus. High level of stenoendemism of subterranean beetle fauna of Mt. Krim calls for urgent regional prioritization for biodiversity conservation at European and global level.
Keywords: beetles; Carabidae; Curculionidae; Dinaridi; Dinarids; endemism; endemiti; hrošči; karst; kras; Leiodidae; podzemeljska favna; Slovenia; Slovenija; Staphylinidae; subterranean fauna